Altered human gut dendritic cell properties in ulcerative colitis are reversed by Lactobacillus plantarum extracellular encrypted peptide STp. Issue 5 (18th December 2013) - Al‐Hassi, Hafid O.; Mann, Elizabeth R.; Sanchez, Borja; English, Nicholas R.; Peake, Simon T.C.; Landy, Jonathan; Man, Ripple; Urdaci, Maria; Hart, Ailsa L.; Fernandez‐Salazar, Luis; Lee, Gui Han; Garrote, Jose A.; et al.
<x xml:space="preserve">Abstract</x> Scope The human/microbiota cross‐talk is partially mediated by bacteria‐derived peptides like Serine‐Threonine peptide (STp), which is resistant to gut proteolysis, is found in the human healthy colon and induces regulatory properties on gut dendritic cells (DCs); here we characterized human gut DC in ulcerative colitis (UC) patients and studied the effect of STp on their properties. Methods and results Human colonic DC from healthy controls and UC patients were isolated, conditioned for 24 h +/− STp and characterized by flow cytometry, immunohistochemistry, and electron microscopy. Expression of immature DC markers DC‐SIGN and ILT3, and Toll‐like receptors were increased on gut UC‐DC. Langerin (involved in phagocytosis), lymph node homing marker CCR7, and activation markers CD40/CD80/CD86 were decreased in UC. Gut DC had restricted stimulatory capacity for T‐cells in UC. Conditioning of DC with STp in vitro reduced Toll‐like receptor expression, increased CD40 and CD80 expression, and restored their stimulatory capacity. Conclusion Colonic DCs display an abnormal immature phenotype in UC, which was partially restored following STp treatment. Bacteria‐derived metabolites, like STp, seem to have a role in gut homeostasis that is missing in UC so they might lead a new era of probiotic products setting the basis for nondrug dietary therapy in inflammatory bowel disease.